Density Functional Theory An Advanced Course - Engel, Eberhard; Dreizler, Reiner M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Density Functional Theory (DFT) has firmly established itself as the workhorse for the atomic-level simulation of condensed matter phases, pure or composite materials and quantum chemical systems. The present book is a rigorous and detailed introduction to the foundations up to and including such advanced topics as orbital-dependent functionals and both time-dependent and relativistic DFT. Given the many ramifications of contemporary DFT, this text concentrates on the self-contained presentation of the basics of the most widely used DFT variants. This implies a thorough discussion of the corresponding existence theorems and effective single particle equations, as well as of key approximations utilized in implementations. The formal results are complemented by selected quantitative results, which primarily aim at illustrating strengths and weaknesses of a particular approach or functional. DFT for superconducting or nuclear and hadronic systems are not addressed in this work. The structure and material contained in this book allow for a tutorial and modular self-study approach: the reader will find that all concepts of many-body theory which are indispensable for the discussion of DFT - such as the single-particle Green$1 (Bs function or response functions - are introduced step by step, rather than just used. The same applies to some basic notions of solid state theory, as, for instance, the Fermi surface. Also, the language of second quantization is introduced systematically in an Appendix for readers without a formal theoretical physics background.s
Introduction -- Foundations of Density Functional Theory: Existence Theorems -- Effective Single-Particle Equations -- Exchange-Correlation Energy Functional -- Virial Theorems -- Orbital Functionals: Optimized Potential Method -- Time-Dependent Density Functional Theory -- Relativistic Density Functional Theory -- Further Reading -- Appendices: Functionals and the Functional Derivative -- Second Quantization in Many-Body Theory -- Scaling Behavior of Many-Body Methods -- Explicit Density Functionals for the Kinetic Energy: Thomas-Fermi Models and Beyond -- Asymptotic Behavior of Quasi-Particle Amplitudes -- Quantization of Noninteracting Fermions in Relativistic Quantum Field Theory -- Renormalization Scheme of Vacuum QED -- Relativistic Homogeneous Electron Gas -- Renormalization of Inhomogeneous Electron Gas -- Gradient Corrections to the Relativistic LDA -- Gordon Decomposition -- Some Useful Formulae -- Index.
Keywords: Physics; Chemistry, Physical and theoretical; Atoms; Condensed matter; Materials science; Physics; Atomic, Molecular, Optical and Plasma Physics; Theoretical and Computational Chemistry; Numerical and Computational Physics; Condensed Matter Physics; Materials Science, general; Electronic books